Muslim parents' reluctance to save for children's tertiary education in Malaysia: causes and reasons - Abd. Hadi, Fatimah-Salwa; Mohd Hussin, Mohd Yahya; Muhammad, Fidlizan; Nawi, Aliff; Mohemed Shaarani, Ahmad Zakirullah; Abdul Razak, Azila; Mahjom, Nurhanie; Ahmad, Mohamad Azahari; Mohd Thas Thaker, Mohamed Asmy (Innovare Academics Sciences Pvt. Ltd, 2020)
This study aimed to identify the reasons and causes for the reluctance of Muslim parents to save for children’s tertiary education despite Islam encouraging the practice of saving money for the future. Additionally, this paper also identified the main sources used for current enrolled college children. A set of questionnaires had been used as the instrument to gather information needed. The respondents of this study were Muslim parents whose children were studying in public higher education institutions in Malaysia. Only 752 questionnaires were considered as completed and usable for analysis. Items in the questionnaires were adopted from Ipsos Public Affairs and adapted according to the suitability of the study. The study employed descriptive analysis including frequency and percentage. The findings showed that all respondents acknowledged that Islam encourages them to save money. The study also proved that T20 and M40 groups were focusing on other saving priorities rather than on children's education. Unlike the previous group (T20 and M40), the B40 group declared that they did not have enough money to save for their children’s tertiary education. B40 also expected that scholarship or financial aid would be enough to cover the cost. Furthermore, since respondents did not have savings for tertiary education of children, they used a variety of resources to finance their children's education. For T20 and M40, parents, their income and savings were used as the main sources for current enrolled college children. For the B40 group, the main sources were children's study loans, current income, scholarship and others. Some B40 received zakat to cover the cost of education. All parties should play their role to make better education possible. In conclusion, the public should be encouraged to save money as early as possible to ensure enough savings in the future. The government should step up with more campaigns and activities to encourage the society to save. Some suggestions to encourage individuals to save more in education were also made.